Seroprevalensi Trichinellosis pada Babi Hutan di Kabupaten Bengkulu Tengah, Provinsi Bengkulu - Milda Lestari; Fadjar Satrija; Risa Tiuria (Jurnal Ilmu Pertanian Indonesia, 2018)
Trichinellosis is a zoonotic disease caused by nematode of the genus Trichinella infection. Transmission of this disease in humans occurs because of eating meat, especially pork containing Trichinella spp. larvae in raw or undercooked conditions. Data on trichinellosis cases in humans and animals in Indonesia are still very limited. This study was carried out to identify the seroprevalence of Trichinella spp. in wild boar in Central Bengkulu District and the level of public knowledge about trichinellosis. Sampling method was used cross sectional method by taking blood serum sample from captured wild boar at TPH in Talang Boseng of Bengkulu Province. Result of serological test using indirect ELISA showed seroprevalence of trichinellosis was 68.2% of total 44 samples obtained. Seropositive results based on the sub-district of the wild boar captured were 12 of 18 (66.7%) in Pondok Kubang and 18 of 26 (69.2%) in Pondok Kelapa. All wild boar meat consumer respondents did not understand that consumption of wild boar meat could become the source of trichinellosis transmission.